Forging New Educational Horizons: Unveiling Virtual Extracurricular Transformation in High School Amidst the COVID- 19 - Lailatussaadah, Lailatussaadah; Jamil, Asyraf Isyraqi Bin; Kadir, Fakhrul Adabi Bin Abdul (Idarah (Jurnal Pendidikan dan Kependidikan), 2023)
Abstract: The educational landscape has undergone significant transformations in the wake of the COVID-19 pandemic, with one notable change being the adoption of virtual platforms for conducting extracurricular activities. This approach marks a departure from traditional practices, as these activities were previously never executed in such a manner. Therefore, this study aims to identify the various forms of virtual implementation of extracurricular activities during the COVID-19 pandemic. In this study, a mixed-methods approach is intended to analyze needs as an initial step in designing the implementation of extracurricular activities during the pandemic. Data was gathered through interviews with the deputy head of the student affairs department and teachers, as well as quantitative data gathered through questionnaires distributed to 20 students from SMAN 3 Banda Aceh. An interactive model and percentage statistics were then used to analyze the data. According to the conclusions drawn from the needs analysis, students chose to implement extracurricular activities in two ways: virtually and non-virtually. Video editing (27.8%), spelling bee (27.8%), cooking class (16.7%), and vocal solo (5.6%) were the four most popular virtual activities. As a result, it is reasonable to deduce that students opted to persist with virtual implementations of extracurricular activities amidst the COVID-19 pandemic, particularly placing emphasis on these four highlighted activities. Subsequent to this research, a study will be undertaken to formulate the design and procedural framework for the execution of extracurricular activities amid the COVID-19 pandemic. Abstrak: Perubahan besar dalam dunia pendidikan telah terjadi pasca pandemic Covid-19. Salah satunya adalah pelaksanaan kegiatan ekstrakurikuler yang dapat dilaksanakan secara virtual, padahal hal itu belum pernah dilakukan sebelumnya. Penelitian ini bertujuan untuk mengidentifikasikan bentuk-bentuk pelaksanaan kegiatan ektrakurikuler yang dapat dilaksanakan secara virtual/daring pada masa pandemi covid-19. Penggunaan metode mix method dalam penelitian ini bertujuan untuk melakukan analisis kebutuhan sebagai sebuah kegiatan awal dalam melakukan rancang bangun terhadap pelaksanaan kegiatan ekstrakurikuler pada masa pandemi covid-19. Pengumpulan data dilakukan melalui wawancara pada wakil kepala bidang kesiswaan, guru, dan data kuantitatif melalui angket yang disebarkan kepada 20 orang siswa SMAN 3 Banda Aceh, selanjutnya data dianalisis dengan model interaktif dan statistic persentase. Hasil penelitian dari analisis kebutuhan menunjukkan bahwa siswa memilih kegiatan ekstrakurikuler diilaksanakan dalam dua cara, yaitu secara virtual dan non virtual. Untuk kegiatan virtual ditemukan 4 kegiatan yang sangat diminati siswa, yaitu video editing sebanyak 27,8%, speling bee sebanyak 27,8%, kelas memasak sebanyak 16,7%, vocal solo 5,6%. Dengan demikian dapat disimpulkan peserta didik memutuskan tetap melaksanakan kegiatan ekstrakurikuler pada masa pandemic covid-19 secara virtual dengan kegiatan 4 kegiatan tersebut. Penelitian ini akan dilanjutkan dengan penelitian pengembangan rancang bangun langkah kegiatan ektrakurikuler pada masa pandemi covid-19.